Deleterious associations of sitting time and television viewing time with cardiometabolic risk biomarkers: Australian Diabetes, Obesity and Lifestyle (AusDiab) study 2004-2005 - Thorp, A.; Healy, Genevieve; Owen, N.; Salmon, J.; Ball, K.; Shaw, J.; Zimmet, P.; Dunstan, D. (American Diabetes Association, 2010)
OBJECTIVE - We examined the associations of sitting time and television (TV) viewing time with continuously measured biomarkers of cardio-metabolic risk in Australian adults. RESEARCH DESIGN AND METHODS - Waist circumference, BMI, resting blood pressure, triglycerides, HDL cholesterol, fasting and 2-h postload plasma glucose, and fasting insulin were measured in 2,761 women and 2,103 men aged =30 years (mean age 54 years) without clinically diagnosed diabetes from the 2004-2005 Australian Diabetes, Obesity and Lifestyle (AusDiab) study. Multivariate linear regression analyses examined associations of self-reported sitting time and TV viewing time (hours per day) with these biomarkers, adjusting for potential confounding variables. RESULTS - For both women and men, sitting time was detrimentally associated with waist circumference, BMI, systolic blood pressure, fasting triglycerides, HDL cholesterol, 2-h postload plasma glucose, and fasting insulin (all P < 0.05), but not with fasting plasma glucose and diastolic blood pressure (men only). With the exception of HDL cholesterol and systolic blood pressure in women, the associations remained significant after further adjustment for waist circumference. TV viewing time was detrimentally associated with all metabolic measures in women and all except HDL cholesterol and blood pressure in men. Only fasting insulin and glucose (men only) remained deleteriously associated with TV viewing time after adjustment for waist circumference. CONCLUSIONS - In women and men, sitting time and TV viewing time were deleteriously associated with cardio-metabolic risk biomarkers, with sitting time having more consistent associations in both sexes and being independent of central adiposity. Preventive initiatives aimed at reducing sitting time should focus on both nonleisure and leisure-time domains. © 2010 by the American Diabetes Association.